STUDI UKURAN BUTIR PASIR DI WILAYAH KERENG BANGKIRAI KOTA PALANGKA RAYA: SIZE STUDY OF SAND GRAINS IN THE KERENG BANGKIRAI AREA, PALANGKA RAYA CITY - Putrawiyanta, I Putu (JURUSAN TEKNIK PERTAMBANGAN UPR, 2023)
The morphological condition of Palangka Raya City which is dominated by a relatively flat area and part of it is a swamp area and flood runoff, causing a lot of accumulation of river sediments in the form of loose material such as sand and clay which are quite thick. Sebangau Subdistrict is one of the subdistricts that has the potential for thick sand deposits, which have been mined by the local community to be used as a mixture of building materials. It is necessary to know the grain size of this grayish-white sand, better known as quartz sand, before mapping out how many potential resources and reserves exist in Sebangau District. It is known from the research results, that most of the grain size of the sand in the research location is Medium Sand with a percentage of 41.29%, then Coarse Sand grain size is 23.65%, Fine Sand grain size is 21.80%, Very Fine Sand grain size is 13 .11%, and a grain size of 0.15% Very Coarse Sand. Keywords: Grain Size, Potential, Sand, Resources